Features of Inheritance of Cryptocurrency Assets - Oleksandr Omelchuk; Inna Iliopol; Snizhanna Alina (Ius Humani. Jornal do direito, 2021)
The article analyzes the legal nature and specific of legal regulation of cryptocurrency in order to reveal the features of inheritance of cryptocurrency assets. The article aims to reveal whether it is possible to inherit cryptocurrency in terms of the existent legislation and if so, what kind of peculiarities of cryptocurrency should be considered. The financial and legal nature of cryptocurrency are described in the article. The main differences between cryptocurrency and traditional electronic money are revealed. The current legislation of Ukraine and some European countries on cryptocurrency legal status is analyzed. It is stated, that in most countries of the world, cryptocurrency is not considered to be money or currency, but rather a kind of property. It is noted, that while solving the issue of inclusion of cryptocurrency assets in the legacy, it is necessary to take into account the functional features of cryptocurrencies in general and the specifics of a particular type of cryptocurrency. Most of the benefits of cryptocurrencies for their owner (such as anonymous character) are obstacles to their inheritance according to the procedures provided by applicable law. The classification of the methods of inheritance of cryptocurrency assets is made in the article. The differences in the inheritance of cryptocurrency and tokens are revealed.